Developing the Product Carbon Footprint for Polymer-based Chemicals via a Life Cycle Assessment Approach - Yue Dian Tan; Gaurav Shukla; Zainuddin Abd. Manan; Sharifah Rafidah Wan Alwi; Jeng Shiun Lim (Chemical Engineering Transactions)
In the pursuit of mitigating the adverse environmental impacts of industrial activities, the concept of product carbon footprint (PCF) has gained significant traction in recent years, especially for polymers and plastics that are difficult to degrade naturally. To evaluate the global warming potential of polymer-based chemicals, this study assesses the PCF of Chemical A produced by a chemical plant in Malaysia. The analysis follows ISO 14067:2018 and the PCF Guideline for the Chemical Industry, considering a cradle-to-gate approach for the fiscal year 2021. The results indicate significant carbon emissions at various life cycle stages of polymer, in which the material acquisition stage was identified as the GHG hotspot contributing 77 % to Chemical A’s PCF. One kg of Chemical A produced is associated with an emission of 3.73 kg carbon dioxide equivalent (CO2e). The study highlights areas for potential environmental improvement from the sourcing of energy and raw materials, to outline corporate sustainability strategies and serves as a model for other chemical companies.